PENGELOMPOKAN WIRAUSAHA BERDASARKAN POTENSI KEWIRAUSAHAAN DENGAN MENGGUNAKAN CARLAND ENTREPRENEUR INDEX (SURVEY PADA PENGUSAHA SANITAER DI KOTA JAMBI) - Erwita Dewi (Jurnal Manajemen Terapan dan Keuangan, 2018)
This research entitled Entrepreneurship Grouping Based on Entrepreneurial Potential Using Carland Entrepreneur Index (Survey on Entrepreneur Sanitaer in Jambi City). The purpose of this study is to know the grouping of entrepreneurs based on their entrepreneurial potential. This research was conducted by using survey analysis by sending questionnaire to sample company then analyzed by using carland entrepreneurship index. The object of this research is sanitaer company in Jambi city. Aiasan selected sanitaer company because it is one of the businesses that participate in realizing sustainable economic development. Sanitaer Enterprises provide the need for sanitary products, ventilation and devices for building roads and buildings. The production of sanitaer's business is used for the development of other industries, namely Agriculture, property industry and transportation industry. So the existence of sanitaer business has an important role in Inclonesia's economic development. The results of this study indicate that the company sanitaer in Jambi most (73.33%) rnenjalankan business with a relatively small initial capital of under 50 million rupiah. The number of employees who work at sanitaer companies in Jambi city mostly (66.67%) less than 10 employees. Based on the analysis of entrepreneurship potential with Carland Entrepreneurship Index (CEI), sanitaer entrepreneurs in Jambi City can grouped into 2 groups, as many as 3 entrepreneurs enter in micro entrepreneurs with a distinctive feature of looking at businesses as a primary source of family income and providing jobs for their families. While as many as 12 entrepreneurs enter into groups of entrepreneurs (entrepreneurs) with their characteristic pursuit of wealth and appreciation. An entrepreneur will be innovative, but they prefer to improve existing products, services and procedures rather than looking for new approaches.